Polyisoprenoid Compounds from Tropical Fruit Trees in Universitas Sumatera Utara Campus - Muttia Chandraputri Rizkiany; Rizka Amelia; Yuntha Bimantara; Hiroshi Sagami; Mohammad Basyuni (Science and Technology Indonesia, 2021)
Tropical trees are a source of secondary metabolite compounds that have various biological activities that can help human life both for industrial and pharmaceutical needs. One of the secondary metabolites is polyisoprenoid. This study aims to identify and analyze polyisoprenoid compounds quantitatively from tropical fruit trees at the Universitas Sumatera Utara. Nine samples of tropical fruit were obtained, namely: Psidium guajava, Tamarindus indica, Manilkara kauki, Morinda citrifolia, Mangifera indica, Artocarpus communis, Artocarpus heterophyllus, Gmelina arborea, and Syzygium aqueum. Each sample was extracted and isolated the polyisoprenoid alcohol, then analyzed using two-dimensional thin-layer chromatography. The polyisoprenoid in fruit samples found at the Universitas Sumatera Utara was a type II and III polyisoprenoid compound. The total lipid values ranged from 48.7 mg/g dw to 262.9 mg/g dw, polyisoprenoids ranged from 1.2 mg/g dw to 9.5 mg/g dw, and polyprenols ranged from 0.5 mg/g dw to 5.7 mg/g dw. Carbon chain length and dolichol polyprenol lengths of each fruit were collected (Psidium guajava L.) (C70 C80), (Tamarindus indica L.) (C80 C95), (Manilkara kauki L.) (C80 C95 and C70 C90), (Morinda citrifolia L.) (C75 C100), (Mangifera indica L.) (C80 C90 and C75 C90), (Artocarpus communis) (C75 C95), (Artocarpus heterophyllus) (C70 C75 and C70 C100), (Gmelina arborea Roxb.) (C90 C95), and (Syzygiumaqueum) (C65 C90 and C75 C90).